Estrutura intelectual da literatura científica do Brasil e outros países dos BRICS: uma análise de cocitação de periódicos na área de célula-tronco - Machado, Raymundo das Neves (2015)
Stem cells research has provided advances with great intervention potential in the field of health, arousing curiosity of both scientific community and citizens. Stem cells are cells that have the ability to self-renew and differentiate into other specialized cells. The search for a better understanding of these processes has been the focus of current studies in this area. This is a relatively new field of knowledge in the world, in which Brazil has been increasingly highlighting in the global science arena, since it is one of the few countries to hold the induced pluripotent stem cells technology, which allows scientists to obtain stem cells in laboratories and so the research in this area. Considering, then, the prominent role of Brazil in this field, this study starts from the following research question: what is the intellectual structure of the scientific literature of the stem cells area in Brazil and other countries from BRICS? It aims, therefore, mapping the intellectual structure of the stem cells area of the Brazilian scientific production in the context of BRICS countries (comprising, besides Brazil, China, Russia, India and South Africa) in two periods 1991-2000 and 2001-2010. The analysis were carried on original articles, recovered from Web of Science database. The method had an exploratory and descriptive approach, and used bibliometric techniques, mainly the analysis of co-citation journals, and cited periodicals were the unit of analysis. The results point to a growth of BRICS scientific production in the whole period, especially after 2001. We found that it had an exponential growth (r² = 0.97), with a doubling time of 2.3 years and growth rate of 37.75% which demonstrates an intense speed production in a dynamic area as stem cells. The ranking positions of scientific output for the BRICS changes from one period to another: Russia leading in the first, followed by China, India, Brazil and South Africa (1991-2000) and in the second China is in the first position followed by Brazil, Russia, India and South Africa. The intellectual structure of BRICS scientific production for the first period (1991-2000) was related more to applied research, with emphasis on topics related to hematology and similar areas. In the second period (2001-2010), BRICS intellectual structure of the scientific production focused on basic research, with attention to cell biology topics, molecular biology and biochemistry, but also considered issues of emerging nature, such as dentistry, neuroscience, cardiology, ophthalmology and biomaterials. The intellectual framework, which was based on co-cited journals, showed a dynamic and interdisciplinary collection that matches the area under study. For the first period, the intellectual framework was guided in the co-cited journals as Blood Cell, Hematology Experimental, British Journal of Haematology, Bone Marrow Transplantation, Cancer Research, Journal of Experimental Medicine and Journal of Immunology; and for the second period, Stem Cells, Cell, Journal of Biological Chemistry, Biomaterials, Development, Journal of Neuroscience, Blood, Cancer Research, Bone Marrow Transplantation and Circulation. The data set indicates that the stem cells research in Brazil, compared to the other BRICS countries, presents both in the aspect of basic and applied research in the area of therapies stem cells. From the results obtained, new research questions appear in order to better understand an area constantly evolving, as stem cells, enabling applications of different co-citation techinques or other with multiple methodological approaches.